CALCULATIONS OF EQUILIBRIUM THERMODYNAMIC PROPERTIES OF METHANE ON THE BASIS OF THE CLUSTER MODEL OF GAS - Kurlapov, L. I.; Janbekova, G. I.; Skornyakov, A. A. (Recent Contributions to Physics, 2008)
Calculations of concentration of clusters, the compressibility factor and molar mass of molecular-cluster mixture of methane under various conditions are given
Keywords: methane